2002
DOI: 10.1016/s0009-2614(02)00670-x
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly hysteresis and slow relaxation of the magnetization in (Et4N)3Fe2F9: manifestations of a single-molecule magnet

Abstract: Abstract(Et 4 N) 3 Fe 2 F 9 exhibits a butterfly-shaped hysteresis below 5 K when the magnetic field is parallel to the threefold axis, in accordance with a very slow magnetization relaxation in the timescale of minutes. This is attributed to an energy barrier ∆ = 2.40 K resulting from the S = 5 dimer ground state of [Fe 2 F 9 ] 3− and a negative axial anisotropy. The relaxation partly occurs via thermally assisted quantum tunneling. These features of a single-molecule magnet are observable at temperatures com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
5
18
1
Order By: Relevance
“…It should be noted that such features of the magnetic behavior as butterfly‐shaped hysteresis and the divergence of FC and ZFC magnetizations can also occur in single molecule magnets (SMMs) or in spin glasses. One can mention in this context the study of (Et 4 N) 3 Fe 2 F 9 SMM, in which the observed butterfly shape hysteresis has been explained as arising from the phonon avalanche effect . However, in the present case no frequency dependence of AC susceptibility has been observed (see Figure ), which rules out the possibility of SMM or spin glass behavior.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…It should be noted that such features of the magnetic behavior as butterfly‐shaped hysteresis and the divergence of FC and ZFC magnetizations can also occur in single molecule magnets (SMMs) or in spin glasses. One can mention in this context the study of (Et 4 N) 3 Fe 2 F 9 SMM, in which the observed butterfly shape hysteresis has been explained as arising from the phonon avalanche effect . However, in the present case no frequency dependence of AC susceptibility has been observed (see Figure ), which rules out the possibility of SMM or spin glass behavior.…”
Section: Resultssupporting
confidence: 49%
“…One can mention in this context the study of (Et 4 N) 3 Fe 2 F 9 SMM, in which the observed butterfly shape hysteresis has been explained as arising from the phonon avalanche effect. [30] However, in the present case no frequency dependence of AC susceptibility has been observed (see Figure 6), which rules out the possibility of SMM or spin glass behavior. At the same time, by applying DC magnetic field of 10 kOe, one can strongly modify the temperature dependence of the in-phase signal (Figure 6), this being in favor of the hypothesis about metamagnetism.…”
Section: Magnetic Propertiescontrasting
confidence: 43%
“…For these molecules the magnetic relaxation is fast. 4 ], many other clusters have been shown to exhibit the same phenomenon, with nuclearities reaching 84, as observed in the giant {Mn 84 } [1] torus reported by Christou et al The maximum ground spin-state ever attained is 83/2 reported for a {Mn 19 } complex by Powell et al [2] However, smaller molecules have been reported to exhibit slow relaxation of their magnetization, like mononuclear Co II [3,4] and Ln III (Ln = Tb, Dy) complexes [5] or dinuclear Fe III , [6] Mn III , [7] Tb III -Cu II [8] and Fe III -Dy III [9] clusters. These species are particularly interesting as their small size allows us to study their electronic properties with exact methods, and fewer approximations.…”
Section: Introductionsupporting
confidence: 60%
“…In this field, the minimization of the SMM nuclearity remains an important issue for obtaining simple model systems with a small number of quantum energy levels. To date, although some claims have been made that mononuclear10, 11 or dinuclear iron systems12 could display SMM or SMM‐like behavior, the smallest complexes unambiguously exhibiting SMM behavior are tetramers of transition metals 3ad. 4b4d, 5c, 6, 7 Herein we report a simple out‐of‐plane Mn III dimer possessing an S T =4 spin ground state and exhibiting slow relaxation of its magnetization at low temperatures with the signature of SMM behavior.…”
mentioning
confidence: 88%